THE EFFECT OF THE COMBINATION OF KEPOK BANANA HEART AND DRAGON FRUIT SKIN ON THE CHEMICAL AND SENSORY PROPERTIES OF HIGH-FIBER ANALOG DENGENG - Shefannia Christy Wijaya; Kejora Handarini; Bambang Sigit Sucahyo; Dewi Mariyanah (RADJA PUBLIKA, 2026)
Food diversification based on local ingredients is needed to produce alternative food products that are high in nutritional value and environmentally friendly. Analog jerky is a plant-based processed product that resembles beef jerky and has the potential to be a high-fiber ready-to-eat food. This study aims to analyze the effect of the proportion of kepok banana blossom ( Musa paradisiaca ) and red dragon fruit peel ( Hylocereus polyrhizus ) on the chemical and organoleptic properties of analog jerky and determine the best proportion. The study was conducted experimentally in a laboratory using a one-factor Completely Randomized Design (CRD) with four treatments, namely the ratio of banana blossom to dragon fruit peel P1 (90%:10%), P2 (70%:30%), P3 (60%:40%), and P4 (50%:50), each with three replications. The parameters analyzed included water content, protein, and crude fiber, the data obtained were analyzed using Analysis of Variance (ANSIRA) and continued with the Least Significant Difference (LSD) test if there was a significant difference. Organoleptic tests were conducted using the hedonic method for color, aroma, and taste, using Kruskal–Wallis non-parametric analysis . The results showed that variations in the proportion of kepok banana blossom and dragon fruit peel significantly affected the water content and protein of analog jerky. Treatment P4 produced the highest protein and crude fiber content, while organoleptic tests showed significant differences in color attributes, but not in aroma, taste, and texture. Overall, treatment P4 was the best formulation because it increased nutritional value without reducing the level of sensory acceptance.